Clonal analysis in recurrent astrocytic, oligoastrocytic and oligodendroglial tumors implicates IDH1-mutation as common tumor initiating event - Lass, Ulrike; Herold-Mende, Christel; Deimling, Andreas von; Müller, Wolf C. (PLOS ONE, 2012)
Background: To investigate the dynamics of inter- and intratumoral molecular alterations during tumor progression in recurrent gliomas. Methodology/Principal Findings: To address intertumoral heterogeneity we investigated non- microdissected tumor tissue of 106 gliomas representing 51 recurrent tumors. To address intratumoral heterogeneity a set of 16 gliomas representing 7 tumor pairs with at least one recurrence, and 4 single mixed gliomas were investigated by microdissection of distinct oligodendroglial and astrocytic tumor components. All tumors and tumor components were analyzed for allelic loss of 1p/19q (LOH 1p/19q), for TP53- mutations and for R132 mutations in the IDH1 gene. The investigation of non- microdissected tumor tissue revealed clonality in 75% (38/51). Aberrant molecular alterations upon recurrence were detected in 25% (13/51). 64% (9/14) of these were novel and associated with tumor progression. Loss of previously detected alterations was observed in 36% (5/14). One tumor pair (1/14; 7%) was significant for both. Intratumoral clonality was detected in 57% (4/7) of the microdissected tumor pairs and in 75% (3/4) of single microdissected tumors. 43% (3/7) of tumor pairs and one single tumor (25%) revealed intratumoral heterogeneity. While intratumoral heterogeneity affected both the TP53- mutational status and the LOH1p/19q status, all tumors with intratumoral heterogeneity shared the R132 IDH1- mutation as a common feature in both their microdissected components. Conclusions/Significance: The majority of recurrent gliomas are of monoclonal origin. However, the detection of divertive tumor cell clones in morphological distinct tumor components sharing IDH1- mutations as early event may provide insight into the tumorigenesis of true mixed gliomas.